Contextual Teaching Learning (CTL) Approach towards Students’ Self Confidence in Learning English; does it have any Effect? - Dedi Sumarsono1; Saiful Amin (Cordova Journal : languages and culture studies, 2019)
In teaching English Language, self-confidence is one psycological aspect that play crucial role for the students. Self-confidence is the positive power or willingness that has a good effect for students during conversation or discussion. Willingness is created when students clearly comprehend what to do and why. Optimism is a mental attitude, optimism is a form of positive thinking that includes the belief that you are responsible for your own happiness (Keller; 2010). To lift the students’ self-confidence in learning English, English language materials that based on the context or real world need to be used in the teaching and learning process. This paper is aimed at knowing the effect English language material which is based on contextual teaching learning towards students’ self confidence in learning English. To achieve this purpose, the students were taught using English language material which is based on contextual teaching learning before the speaking test was taken at the end. To analyze the data t-test was applied. The data analysis shows that students’ self confidence in learning English is improved but it doesn’t give significantly affect towards the students’ self-confidence.